National Social Science Survey, 1994 - Kelley, Jonathan (ADA Dataverse, 2019)
This file is the seventh in the National Social Science Survey (NSSS) series and repeats many of the questions asked in the previous rounds. The survey also includes questions asked as part of the International Social Survey Programme. Comparative data from all countries in the Programme are processed and distributed by the Zentralarchiv fur Empirische Sozialforschung (ZA) at the University of Cologne (Private Business and Government Enterprises, and Environment II). The data file contains a wide range of attitudinal questions. Sections cover attitudes to government policies; trade unionism; attitudes to political leaders, parties and election issues; voting and party identification; feeling thermometer ratings of political leaders, groups and institutions; standard of living when growing up and now; courtship and marriage; abortion; euthanasia; religious beliefs and behaviours; sexual relations; working women. The Private Business and Government Enterprises module covers quality of private business and government enterprises. The Inequality module covers government regulation of business; importance of hierarchical pay structure; estimates of actual and ideal salaries for various work positions; conflicts between social groups; deciding factors in pay rates; actual and ideal social structure, and respondents' position in the structure. The Environment module includes opinions on science and nature, government involvement in environmental protection; pollution and the effects on the environment and health; behaviours to protect the environment, such as recycling; and environmental group membership. Background variables include respondents' occupation, education and qualifications; income, assets and standard of living; trade union membership, political orientation, and religion; birthplace of parents and grandfathers, education and political orientation of parents and spouse, education of grandfathers, children and siblings.